LESSON LEARNED AFTER THE FIRST WAVE OF THE COVID-19 PANDEMIC IN THE REPUBLIC OF NORTHERN MACEDONIA - Liljana Ignjatova (Prohealth Ljubljana, Slovenija, 2020)
What we have known so far is that crises do not affect everyone equally and that they mostly affect the most vulnerable categories (people who use drugs, certain ethnic communities, sex workers, etc.). What we learned after the first wave of the COVID-19 crisis is described in this article. Online counseling in youth counseling centers for prevention of psychoactive substance use was not equally applicable in all settings, such as the Roma community for example. In the youth counseling centers for prevention of substance use, the number of visits by young people with “covid induced / triggered anxiety” has increased, as well as young people who coping the anxiety with alcohol and others substances. Problematic use of the Internet has increased. The flexibility of drug treatment and care programs has reduced the drop-out rate of people receiving opioid agonist treatment (OAT). Access to programs and decentralized work model across the country have also reduced treatment dropouts. The presence of all staff working with drug users at the services most of the time, the admissions that were realized immediately without waiting lists and postponed appointments and in any circumstances (in quarantines - hotels, hospitals, etc.) as wall as reduced drop-outs have prevented overdoses and suicides of opioid users in the country. The drug problem has not disappeared, it may have changed but not disappeared. The drugs continued to travel. Online drugs were available. New drug victims continued to seek help. Conclusion:We do not have the “privilege” to waive the provision of treatment and care, without delay, for all our patients seeking help no matter where they are, at home, in quarantine or coming to the services. Flexibility and pragmatism, creativity and innovation are needed to provide accessible drug treatment services for all but also the most vulnerable categories that will be specific and created for them to reduce the consequences during the KOVID-19 pandemic.
Keywords: drug use; treatment; COVID-19 pandemic